2012
DOI: 10.1111/j.1745-8315.2011.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical issues in analyses over the telephone and the internet

Abstract: There is professional consensus that teleanalysis, the practice of psychoanalysis conducted remotely using the telephone and the Internet, is increasing in response to more mobility in the population. But there is controversy as to whether the use of technology leads to a dilution of analysis or to adaptive innovation that is clinically effective and true to the tenets of psychoanalysis. The author reviews the psychoanalytic literature and shows the development of analytic thinking about this technology-assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 7 publications
5
60
0
7
Order By: Relevance
“…Atendimento psicoterápico pela internet: história, conceituação e prática Apesar de o atendimento psicoterápico por telefone ser uma prática que remonta à década de 50 (Godleski, Nieves, Darkins, & Lehmann, 2008;Scharff, 2012), a psicoterapia pela internet, em seu início, há mais de uma década, recebeu grande oposição. Acreditava-se que a relação terapêutica ficaria comprometida por um empobrecimento da comunicação não verbal, elemento considerado essencial à interação entre terapeuta e paciente.…”
unclassified
“…Atendimento psicoterápico pela internet: história, conceituação e prática Apesar de o atendimento psicoterápico por telefone ser uma prática que remonta à década de 50 (Godleski, Nieves, Darkins, & Lehmann, 2008;Scharff, 2012), a psicoterapia pela internet, em seu início, há mais de uma década, recebeu grande oposição. Acreditava-se que a relação terapêutica ficaria comprometida por um empobrecimento da comunicação não verbal, elemento considerado essencial à interação entre terapeuta e paciente.…”
unclassified
“…Another explanation for the higher average number of sessions delivered to consumers in receipt of sessions by telephone may be that some telephone sessions may take place on an ad hoc basis if mental health professionals contact 'at-risk' consumers in between face-to-face sessions. Alternatively, it may reflect compensation for a loss of non-verbal cues during telephone sessions and perceived risk to rapport experienced by mental health professionals (Centore and Milacci 2008), although others including the mental health professionals in the present study have suggested that the telephone modality results in more 'intent listening' (Scharff 2012). The uptake of telephone sessions in urban areas was initially slower than in rural areas and this is probably attributable to the fact that the T-CBT pilot itself targeted rural Divisions.…”
Section: Discussionmentioning
confidence: 64%
“…No entanto, se expandir a compreensão da téc-nica psicoterápica psicanalítica aos países que já adotam a psicoterapia a distância, podemos encontrar estudos sob duas diferentes direções, a primeira sob o prisma que encoraja o uso ético e responsável das tecnologias (Carlino, 2011;Scharff, 2012; e a segunda sob o ponto de vista daqueles que clamam por cautela e pela adoção da técnica psicanalítica tradicional (Barbieri, 2005;Russell, 2015). Contudo, como relata Nóbrega (2015), a utilização das TICs em psicoterapia já está acontecendo nos consultórios psicoterápicos muito antes dos próprios profissionais discutirem com os seus pares.…”
Section: Quadrounclassified
“…Em alguns países, como Estados Unidos e Austrália, a prática é reconhecida e aceita e há diversos estudos que discutem como utilizar essas tecnologias a favor da psicoterapia psicanalítica (Carlino, 2011;Crestana, 2015;Scharff, 2012;, já no Brasil a temática parece ser recente e sua discussão ainda incipiente (Hallberg, & Lisboa, 2016;Pieta, & Gomes, 2014;Sffogia et al, 2014). Entretanto, o que a literatura tem evidenciado é que a psicoterapia psicanalítica por meio de tecnologias de informação e comunicação pode promover as mesmas mudanças terapêuticas e mantém a técnica psicanalítica semelhante ao tratamento presencial (Scharff, 2012). Assim, investigações que permitam reflexões sobre a incorporação e manejo dessas práticas no dia a dia do profissional psicoterapeuta parecem merecer atenção de pesquisadores.…”
Section: Introductionunclassified